The Effect of the Hepatitis B Virus Surface Protein Truncated sC69∗ Mutation on Viral Infectivity and the Host Innate Immune Response - Xiang, Kuanhui; Xiao, Yiwei; Li, Yao; He, Lingyuan; Wang, Luwei; Zhuang, Hui; Li, Tong (Frontiers in Microbiology, 2019)
Viruses could rapidly diversify into variants, which has long been known to facilitate viral adaption in the host. Recent studies showed that cooperation among variants and wild-type (WT) also increased viral fitness. Here, a mutant of sC69* in small hepatitis B surface protein (SHBs) that resulted in premature stop was investigated and the frequency of sC69* was 4.37% (19/435), most of which coexisted with the WT (78.95%, 15/19), indicating mixed viral populations. Functional studies showed that sC69* mutant was associated with lower viral spread, but could be rescued by coexisting with the WT. The sC69* mutant showed to attenuate host innate immune response during infection and poly (I:C) treatment such as IL29, ISG15 and RIG-I (p<0.05). The lower immune response was not caused by the lower replication of sC69* mutant. Our data provide information that sC69* coexisting with the WT might facilitate the fitness and persistence of the viral quasispecies in the host.